Optimal scheduling of buildings with energy generation and thermal energy storage under dynamic electricity pricing using mixed-integer nonlinear programming - Lu, Yuehong; Wang, Shengwei; Sun, Yongjun; Yan, Chengchu (Applied energy, 2015)
•Optimal scheduling strategy for building energy systems is developed.•Mixed-integer nonlinear programming approach is used for the optimal scheduling.•Four scenarios are investigated to evaluate the optimal scheduling strategy.•Case studies are conducted on the Hong Kong Zero Carbon Building. The increasing complexity of building energy systems integrated with renewable energy systems requires essentially more intelligent scheduling strategy. The energy systems often have strong non-linear characteristics and have discrete working ranges. The mixed-integer nonlinear programming approach is used to solve their optimal scheduling problems of energy systems in building integrated with energy generation and thermal energy storage in this study. The optimal scheduling strategy minimizes the overall operation cost day-ahead, including operation energy cost and cost concerning the plant on/off penalty. A case study is conducted to validate the proposed strategy based on the Hong Kong Zero Carbon Building. Four scenarios are investigated and compared to exam the performance of the optimal scheduling. Results show that the strategy can reduce operation energy cost greatly (about 25%) compared with a rule-based strategy and the reduction is even increased to about 47% when a thermal energy storage system is used. The strategy can also reduce the on/off frequency of chillers significantly.